Analisis Faktor Penentu Kemandirian Kewirausahaan Inklusif Penyandang Disabilitas: Studi Pada Kota Tangerang Propinsi Banten - Lia Dama Yanti; Vivin Hanitha; Rina Aprilyanti; Citrawati Jatiningrum (eCo-Buss, 2022)
Inclusive entrepreneurship in Indonesia is one of the strategic issues that is the government's priority target. Inclusive business independence through Micro, Small and Medium Enterprises (MSMEs) with disabilities is believed to be one of the solutions to increase the productivity and welfare of persons with disabilities. The purpose of this study is to analyze the determinants of entrepreneurial independence in inclusive businesses for persons with disabilities in the city of Tangerang. This study uses the statistical analysis method of probit regression and multiple linear regression and interview results. The results reveal that several factors influence inclusive entrepreneurship where evidence shown that expertise or skill of disabilities, information access and social support are the most important factors. In addition, inclusive microfinance and digital marketing for persons with disabilities have also proven significant in increasing business independence. This finding has contribute to the government in providing policies and regulations for the entrepreneurial of MSMEs for people with disabilities in Indonesia